Gender, Campus Sexual Violence, Cultural Betrayal, Institutional Betrayal, and Institutional Support in U.S. Ethnic Minority College Students: A Descriptive Study - Gómez, Jennifer M. (Violence against women, 2022)
Women and ethnic minorities are at increased risk for campus sexual violence (CSV). Due to inequality, within-group victimization in marginalized communities includes cultural betrayal. Universities commit institutional betrayal (e.g., inadequate prevention) and institutional support (e.g., sensitivity). With a campus climate survey, the purpose of the study is to characterize, by gender, U.S. ethnic minority undergraduates’ CSV, cultural and institutional betrayal, and institutional support. Participants (N = 222) were a random sample of ethnic minority undergraduates. College women experienced higher rates of CSV and institutional betrayal. Universities can implement a research agenda that centralizes the role of oppression in CSV.